2023
DOI: 10.1590/2179-8087-floram-2023-0016
|View full text |Cite
|
Sign up to set email alerts
|

The Composition and Termicidal Activity of Vinegar from Medang Wood (Cinnamomum sp.) under Different Pyrolysis Temperature

Hasan Ashari Oramahi,
Rizka Diah Permana,
Farah Diba
et al.

Abstract: The degradation of wood caused by termite infestations is widely recognized as a substantial concern. Therefore, the development of alternative, environmentally-friendly preservation of wood is needed to reduce environmental pollution. The study aimed to analyze the chemical properties of vinegar from medang wood (Cinnamomum sp.) and assess its effectiveness as a termicidal activity against Coptotermes curvignathus. Wood vinegar is made by the pyrolysis method. Pyrolysis is carried out by inserting of air-drie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…Oramahi et al (2022a) reported that liquid smoke from Shorea pachyphylla mainly contained formic acid, 2-propanone, acetic acid,4hexadecanoic acid, and guaiacol. Recently, Oramahi et al (2023) investigated that the predominant compounds in liquid smoke gained from Cinnamomum sp. were 1,2-ethanadiol, acetic acid, phenol and methyl ester.…”
Section: Chemical Composition Of Liquid Smoke From Terminalia Catappamentioning
confidence: 99%
“…Oramahi et al (2022a) reported that liquid smoke from Shorea pachyphylla mainly contained formic acid, 2-propanone, acetic acid,4hexadecanoic acid, and guaiacol. Recently, Oramahi et al (2023) investigated that the predominant compounds in liquid smoke gained from Cinnamomum sp. were 1,2-ethanadiol, acetic acid, phenol and methyl ester.…”
Section: Chemical Composition Of Liquid Smoke From Terminalia Catappamentioning
confidence: 99%